Hubungan Pola Asuh Orang Tua Dan Komunikasi Keluarga Dengan Mekanisme Koping Dalam Menghadapi Bullying Pada Remaja Di SMP PGRI 3 Bogor Tahun 2023 - Lulu Muzdalifah; Rindu Rindu; Lannasari Lannasari (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Coping mechanisms are ways that individuals solve problems, resolve themselves with changes that occur and respond to problems and threatening situations. Factors that influence coping mechanisms are parenting in the family which plays an important role in the formation of personality in children, in addition to parenting, family communication is influenced by the way parents interact with children Purpose: To determine the relationship between parenting patterns and family communication with coping mechanisms in dealing with bullying in adolescents at SMP PGRI 3 Bogor. Method: The study used a quantitative design and used a descriptive correlation method with a cross sectional approach, the sampling technique used was random sampling, with a total sample of 88 respondents. Data analysis of this study using the Spearman Rank Test Research Results: There is a relationship between parenting patterns and coping mechanisms in dealing with bullying in adolescents at SMP PGRI 3 Bogor which is shown from the p value (Value) 0.003 with the relationship between the two variables shown at a value of 0.318, there is a relationship between family communication and coping mechanisms in dealing with bullying in adolescents at SMP PGRI 3 Bogor which is shown from the p value (Value) 0.000 with the relationship between the two variables shown at a value of 0.524. Conclusion: This study shows that there is a relationship between parenting and family communication with coping mechanisms in dealing with bullying in adolescents at SMP PGRI 3 Bogor in 2023.